Assessment of Arsenic Concentration in Ground Water of Tube Wells in Selected Primary Schools at Palashbari Upazila of Gaibanda District - Khan, MNH; Rahman, MM; Rokanuzzaman, M (Journal of Environmental Science and Natural Resources, 2012)
Arsenic contamination has been recognized as an acute national problem in Bangladesh. Tube wells, one of the most important source of drinking water in Bangladesh, are contaminated by arsenic in 61 districts out of a total of 64. Children who are exposed to high levels of arsenic in their drinking water are 7 to 12 times susceptible then adult. This study was conducted to know the arsenic concentration level in primary schools tube wells. Twenty seven schools were selected at Palashbari upazila of Gaibandha district under Rangpur division. Econo Quick test kit was used to measure arsenic concentration. Global Positioning System (GPS) was used to indicate the geographic location. Fifteen were Sallow Tube Well no. 06 and eleven were Deep Tube Well no. 06 among the examined tube wells. Arsenic concentration of these studied tube wells were ranged between 0 to 200?g/L. Except two all are below (0 to 10?g/L) the WHO maximum permissible level (50?g/L). Among these two one lies marginal level (50?g/L) and another crosses the level (200?g/L). Arsenic concentrations of these tube wells were not high. So, there could be considered as a safe source of drinking water for the pupils of these primary schools. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10159 J. Environ. Sci. & Natural Resources, 4(2): 115-120, 2011